Proposal for the restructuring of the production and marketing area of the online lady's bakery in the city of Guayaquil, Urdesa sector. - Holguín Cedeño, Ilma Verónica; Mariscal Panchana, Lady Alejandra (Ingeniería Química y Desarrollo, 2024)
In the present work you will find relevant information about the Lady's Bakery online pastry shop that will help the development of the proposed project through which the aspects to work on are determined, such as the marketing area and the production area, both areas present many possibilities of improvements, same for which an improvement proposal has been sought through previous studies on the POES, e-commerce, infrastructure standards, among others, coming to consider it appropriate to internally examine the small business. The investigation has stimulated the creation of the administrative area of ​​the small company from the constitution of this starting from the mission to the corporate image, which is potentiated with a marketing study that responds to the results obtained from the surveys carried out on 336 people between customers and those immersed in online purchases. In addition to this, the aspects to be improved in the production area have been determined, from how the area should be adapted for better work to its lighting and ventilation system. The following degree work is developed through a mixed methodology with the technique of online surveys, as it is a pastry shop that performs its work activities on social networks.
Keywords: restructuring; marketing; production; safety; past